Regular alcohol ingestion: high risk of chronic alcohol intoxication, controversy of protective effects - A. Yu. Nikolaev; A. V. Malkoch (Лечащий Врач)
The review describes modern views on consequences of regular alcohol ingestion for human body. The results of alcohol influence on cardiovascular, nervous, gastrointestinal and other systems of the organism were shown. Controversy of protective effects of low alcohol doses was discussed.